A Survey on Opinion Mining: Applications, Challenges, Tools and Techniques - Prakash, MK; Dinesh, G (International Journal of Computer Sciences and Engineering, 2025)
Opinion Mining is a process of automatic extraction of knowledge by means of opinion of others about some particular product, topic or problem. The idea of Opinion mining and Sentiment Analysis tool is to process a set of search results for a given item based on the quality and features. Opinion Mining is a useful tool for gathering information about customers’ opinions about products, brands or companies. Opinion mining is a type of natural language processing which could track the mood of the people about any particular product by review. Opinion mining is also called sentiment analysis due to large volume of opinion which is rich in web resources available online. Analyzing customer review is most important, by doing that we tend to rate the product and provide opinions for it which is been a challenging problem today. Most of the people watch the user reviews before buying the product. So in that aspect, here analyze and categorize the all the user review i.e opinion, in three types(positive, negative, or neutral). All the positive, negative and neutral comments are categorized in percentage with the pie-chart representation, from the total comments received. This paper focus on the opinion mining applications, challenges, tools and techniques for a particular product, from the customer review.